Topology optimization for custom bed-resting ankle foot orthosis - Ab Rashid, Amir Mustakim; Md Nazid, Effi Zuhairah; Mazlan, Muhammad Hazli; Pangesty, Azizah Intan; Abdullah, Abdul Halim (2023)
The ankle-foot orthosis (AFO) is a widely used aid for people who suffer from weakness of the dorsiflexion muscles of the ankle due to peripheral or central nervous system problems. Both conditions are caused by a lack of dorsiflexion assistance due to muscle weakness. The mobility of the surrounding joints is affected by the deformity and muscle weakness of a lower limb joint, so corrective measures are required. The aim of this study is, therefore, to observe the effects of a topology optimized AFO model on pressure distribution. The product was designed in Solidworks and subjected to finite element analysis using polylactic acid (PLA) to determine the maximum value of Von Mises stress (VMS) and displacement. The design is then optimized using a topology study to analyze the iteration of the component design that meets a specific optimized target and geometric constraints. The final product is expected to have the desired function of the AFO for bedridden patients